O uso dos operadores MAS e EMBORA nos textos argumentativos de discentes da 3ª série do Ensino Médio - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This dissertation, investigates the use of operators but and although in students’ argumentative texts of the 3rd grade of high school. This study aims to examine the route of these textual articulators as well as their deployment adversative and concessive values expressed by them. For this reason, there is a research with qualitative approach, nature documentary and modality based on content analysis, grounded on Linguistic Functionalism, with the help of Textual Linguistic and Semantic Argumentative. The results showed a balance in the number of occurrences (thirty-nine but and forty although), in the corpus. In construction also with negative inference, there were imminence cases (nineteen but and fifteen although). On the other hand, was evidenced a discrepancy in the number of occurrences of the contrast, three occurrences to but and twenty-five to although. But as argumentative semantic values there was something similar: eight occurrences to butSN and twenty-seven to butPA. It was found that the meaning of the operators researched on this analysis, besides the meaning made by syntactic and semantic aspects, put to communicative necessity of writer/reader. So, if the intention is the thriller strategy, (but) is chosen to adversarial reasoning, by the anticipation strategy, (although) is elected as concessive reasoning
Keywords: Operadores argumentativos; Valores adversativos; Valores concessivos; CIÊNCIAS HUMANAS: LINGUÍSTICA, LETRAS E ARTES